Types of messages used by mothers to communicate the children: conversation analysis - Winarti, Oktifani (Faculty of Communications Science, Dr. Soetomo University, 2023)
Using Conversation Analysis, this paper explores the interaction between a mother and their children while giving morality messages. Conversation Analysis breaks down every interaction between a mother and their children to understand the success of interaction for a mother in delivering moral lessons to her children. By using a natural-setting audio recording and exporting the conversation through excerpts of conversations, this paper reveals three interesting findings from their interaction and turn-taking through varieties of turn-design sequences. The findings of this research show there are three ways of interaction used by mothers: 1) future forecasting, 2) authority-evoking, and 3) self-disclosing.